The transformation-mainstreaming conundrum: Making sense of tensions in adaptation practice - Roger Street; Michael Dunlop; Seona Meharg; Russell Gorddard; Yiheyis Maru; Minh N. Nguyen; Deborah O’Connell; Rachel Williams; Russell M. Wise; Mark Stafford Smith (Ambio, 2026)
As the scale of climate change impacts become apparent, organisations globally are seeking to adapt. They face dual imperatives of transformation—going beyond business-as-usual to embrace disruptive changes to their decision-making processes—and mainstreaming—enacting adaptation initiatives with minimal change to existing capabilities and structures. In practice, these important imperatives can conflict, leading to the emergence of multiple tensions in developing and implementing adaptation initiatives, potentially paralysing action or leading to one imperative dominating. We call this the Transformation-Mainstreaming Conundrum (TMC) and suggest that both imperatives can (and must be) pursued simultaneously in practice. This perspective identifies recognisable tensions that can arise when seeking to address both imperatives and suggest steps towards responding to the underlying issues these tensions reveal. The TMC needs to be recognised, and approaches to navigating its tensions must be addressed explicitly in both scholarship and practice, to re-energise the urgency of scaling up adaptation efforts.